Educational psychology in medical learning: a randomised controlled trial of two aide memoires for the recall of causes of electromechanical dissociation. Issue 4 (18th June 2004) - Dyson, E; Voisey, S; Hughes, S; Higgins, B; McQuillan, P J
Abstract : Objectives: Although mnemonics are commonly used in medical education there are few data on their effectiveness. A RCT was undertaken to test the hypothesis that a new aide memoire, "EMD-aide", would be superior to the conventional "4Hs+4Ts" mnemonic in facilitating recall of causes of electromechanical dissociation (EMD) among house officers. Method: "EMD-aide", organises causes of EMD by frequency of occurrence and ease of reversibility: four groups organised by shape, colour, position, numbering, clockwise sequence, and use of arrows. Eight hospitals were randomised in a controlled trial and 149 house officers were then recruited by telephone. Baseline ability to recall causes of EMD was recorded at one minute and overall. House officers were then sent a copy of either "4Hs+4Ts" or "EMD-aide" according to randomisation group. Recall ability was retested at one month. Results: 68 of 80 and 51 of 69 house officers completed the study in the "4Hs+4Ts" and "EMD-aide" groups respectively (NS) with similar baseline recall. After intervention median number of recalled causes was greater in the "EMD-aide" group, eight compared with seven at one minute (p = 0.034) and eight compared with seven overall, p = 0.067. Recall of all eight causes was more common in "EMD-aide" group, 54% compared with 35%, p = 0.054, and these house officers spent longer examining their aide memoire, p<0.001. Conclusions: "EMD-aide" may be superior to "4Hs+4Ts" in facilitating the recall of the causes of electromechanical dissociation. Educational psychology of medical learning and the use of aide memoires in general are worthy of further study.